2014
DOI: 10.3389/fonc.2014.00326
|View full text |Cite
|
Sign up to set email alerts
|

For Stage II Node-Positive Breast Cancer, is it Worthwhile to Consider Adjuvant Radiotherapy Following Mastectomy?

Abstract: Purpose: To evaluate overall survival (OS), progression-free survival (PFS), loco-regional recurrence (LRR), and toxicities for early breast-cancer patients with one to three positive axillary lymph nodes, by the addition of radiotherapy to adjuvant chemotherapy.Patients and methods: Patients were eligible for enrollment into the study if they had pathologically proven stages II breast cancer, with one to three positive axillary lymph nodes. Patients were assigned to one of the two groups; Group 1; adjuvant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This study included 3 randomized controlled trials, 19 , 20 , 21 15 retrospective studies, 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 and 1 prospective study. 37 No case-control studies using radiation therapy within the period assessed in Africa was identified. In total, the 19 included studies recruited 4100 female patients with breast cancer with sample size ranging from 15 to 434 participants per study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study included 3 randomized controlled trials, 19 , 20 , 21 15 retrospective studies, 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 and 1 prospective study. 37 No case-control studies using radiation therapy within the period assessed in Africa was identified. In total, the 19 included studies recruited 4100 female patients with breast cancer with sample size ranging from 15 to 434 participants per study.…”
Section: Resultsmentioning
confidence: 99%
“… 25 , 29 , 34 The remaining 13 studies had no information on the DFS of patients treated with radiation therapy. 19 , 20 , 21 , 22 , 23 , 26 , 27 , 28 , 30 , 32 , 33 , 36 , 37 DFS was measured from the date of enrollment of patients to the date of first event (relapse, progression, or death from any cause) or to the last follow-up date. Based on the study of Osman et al, 37 PFS was calculated from the date of randomization of treatment to relapse, recurrence, or the last follow-up date.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expected 5-year OS by treatment regimen and patient group was estimated with results from clinical trials and studies identi ed through secondary research (10)(11)(12)(13)(14)(15)(16)(17)(18). The OS from the reviewed sources was reported in different time frames or units, for example: median survival or hazard ratio to another known result.…”
mentioning
confidence: 99%